2020
DOI: 10.1002/fsn3.1394
|View full text |Cite
|
Sign up to set email alerts
|

Drivers for the implementation of market‐based food safety management systems: Evidence from Lebanon

Abstract: The food safety landscape continues to evolve across time, geography, and supply chains. This research seeks to analyze the determinants of market‐based food safety management systems (FSMSs) implementation in the Middle Eastern context. Primary data were collected from food safety managers representing 94 processors across Lebanon. We found food processors having implemented ISO 22000 (50%), HACCP (40%), and ISO 9001 (25.5%); however, none of the processors implemented industry‐based FSMSs. Although ISO 22000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 39 publications
0
25
0
2
Order By: Relevance
“…In general, the most emphasis is placed on ISO 22000 and many studies concluded that adoption is more challenging and less likely in small companies [59,60]. Small scale producers are in general less likely to seek ISO certification, which is in part attributed to 'organisational readiness' of small producers [59,61], cost [59,62], and lack of knowledge [62]. However, studies also show that even in the context of small scale producers, ISO standards can serve as a springboard of adoption of multiple productivity enhancing principles-such as lean or requirements of multiple standards [63].…”
Section: Adoption Of Iso Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the most emphasis is placed on ISO 22000 and many studies concluded that adoption is more challenging and less likely in small companies [59,60]. Small scale producers are in general less likely to seek ISO certification, which is in part attributed to 'organisational readiness' of small producers [59,61], cost [59,62], and lack of knowledge [62]. However, studies also show that even in the context of small scale producers, ISO standards can serve as a springboard of adoption of multiple productivity enhancing principles-such as lean or requirements of multiple standards [63].…”
Section: Adoption Of Iso Standardsmentioning
confidence: 99%
“…Based on a review of the literature, Panghal, Chhikara, Sindhu and Jaglan [69] conclude that "ISO 22000 along with its sister standards are auditable, reliable, and reasonable to ensure safe production, distribution, and consumption of food." Salim, Padfield, Chew, Syayuti, Papargyropoulou and Mun Hou [62] assert that the standards have a greater positive impact on larger firms, as smaller firms benefit less due to high implementation cost and lack of knowledge about the requirements of the standards. Păunescu, Argatu and Lungu [64] propose that the main impact is in terms of provision of safer products by reduction of illnesses and other risks.…”
Section: Agricultural Productivity Of Firms That Adopt Iso Standardsmentioning
confidence: 99%
“…Lebanon is considered as a crucial member and commercial partner for the European Union after signing the Euro-Mediterranean agreement in partnership. Therefore, Lebanon offers a stimulating point to gain a better understanding of e-commerce in the Middle East region (Abebe et al 2020). Lebanon has several bilateral and regional trade agreements with the European Union, including the Euro-Mediterranean partnership.…”
Section: Overview Of the Middle East Regionmentioning
confidence: 99%
“…Um estudo na Polônia descreve que a aplicação de um sistema de modelo baseado principalmente na aderência rígida a protocolos de gerenciamento de qualidade em algumas empresas de alimentos de tamanho pequeno a médio pode ser prejudicial em comparação a várias soluções práticas, com foco na simplificação de algumas áreas do sistema, como diagramas de fluxo, análise de perigos, procedimentos e registros documentados e aplicação de manual de BPFs (Dzwolak, 2014). No Líbano, a maioria das empresas de alimentos são pequenas e médias e somente em 27% das pequenas são implementadas BPFs em comparação a 69% de BPFs em empresas consideradas grandes (Abebe, et al, 2020). Particularmente, problemas nas atividades de identificação e avaliação de perigos podem ocorrer quando há uma falta significativa de pessoal treinado em APPCC e / ou altamente treinado em APPCC, por exemplo, este fato ocorre na Sérvia na inspeção de alimentos de origem animal (Tomašević and Đekić, 2017).…”
Section: Depois Antesunclassified
“…qualidade, mas bem menos relevante em comparação com o custo da não conformidade(ABEBE et al, 2020) e ainda há necessidade de treinamento e adesão constante dos colaboradores ao sistema(CUSATO et al, 2013). A qualidade não custa dinheiro e sim gera benefícios.…”
unclassified